From Ephemeral Planning to Permanent Urbanism: An Urban Planning Theory of Mega-Events - Kassens-Noor, Eva (2016)
Mega-events like the Olympic Games are powerful forces that shape cities. In the wake of mega-events, a variety of positive and negative legacies have remained in host cities. In order to bring some theoretical clarity to debates about legacy creation, I introduce the concepts of the mega-event utopia, dystopia and heterotopia. A mega-event utopia is ideal and imaginary urbanism embracing abstract concepts about economies, socio-political systems, spaces, and societies in the host during events. The mega-event utopia (in contrast to other utopian visions other stakeholders may hold) is dictated by the desires of the mega-event owners irrespective of the realities in the event host. In short, a mega-event utopia is the perfect event host from the owner’s perspective. Mega-event utopias are suggested as a theoretical model for the systematic transformation of their host cities. As large-scale events progress as ever more powerful transformers into this century, mega-event dystopias have emerged as negatives of these idealistic utopias. As hybrid post-event landscapes, mega-event heterotopias manifest the temporary mega-event utopia as legacy imprints into the long-term realities in hosting cities. Using the Olympic utopia as an example of a mega-event utopia, I theorize utopian visions around four urban traits: economy, image, infrastructure and society. Through the concept of the mega-event legacy utopia, I also provide some insight toward the operationalization of the four urban traits for a city’s economic development, local place marketing, urban development, and public participation.